BMI and cause‐specific hospital admissions and costs: The UK Biobank cohort study - O’Halloran, R; Mihaylova, B; Cairns, BJ; Kent, S (Wiley, 2020)
Objective To estimate the effect of BMI on cause‐specific hospital admissions and costs in men and women is not well understood, and this study’s aim is to address this.